Professionally important qualities of the head of the middle level in the penitentiary system of Russia - Bovin, B.G.; Iriskhanov, A.A. (Psihologiâ i pravo, 2017)
The article presents the results of an empirical study conducted on a representative sample of the penitentiary system staff. The subject of the study were deputy heads of correctional institutions and heads of departments in various areas of work in the Federal Penitentiary Service of Russia for the North Caucasus Federal District, enlisted in the reserve for higher managerial positions. The purpose of the study is to determine the professionally important qualities (PIQ) of middle managers and to identify potential abilities for managerial activities at a higher position. According to expert estimates, given by immediate supervisors to candidates for the reserve for nomination, the general level of development of the TAC was determined. The psychodiagnostic examination of candidates enrolled in the reserve for nomination, using the methods used in the centers of psychodiagnostics (CPD) of the territorial bodies of the penitentiary system during admission to the service, made it possible to identify potential abilities for responsible higher-level administrative work and psychological contraindications to the employment of a higher middle management. В статье представлены результаты эмпирического исследования, проведенного на репрезентативной выборке сотрудников уголовно-исполнительной системы (УИС). Объектом изучения были заместители руководителей исправительных учреждений и начальники отделов по различным направлениям работы в УФСИН России по Северо-Кавказскому федеральному округу, зачисленные в резерв на вышестоящие управленческие должности. Цель исследования – определение профессионально важных качеств (ПВК) руководителей среднего звена УИС и выявление потенциальных способностей к управленческой деятельности на вышестоящей должности. По экспертным оценкам, даваемым непосредственными начальниками кандидатам в резерв на выдвижение, определялся общий уровень развития ПВК. Психодиагностическое обследование кандидатов, зачисленных в резерв на выдвижение, с использованием методов, применяемых в центрах психодиагностики (ЦПД) территориальных органов УИС при приеме на службу, позволило выявить потенциальные способности к ответственной управленческой работе более высокого уровня и психологические противопоказания к занятию вышестоящей должности руководителя среднего звена.